Implementation of Learning Physical Education Sport and Health at Nature Elementary School Ungaran (Study Program Education and Sports, Postgraduate Universitas Negeri Semarang, 2018)
This study aims to examine and analyze learning physical education in elementary school at Ungaran that includes the stage of planning, implementation phase, assessment phase, facilities and infrastructure, and the level of physical fitness. This qualitative research uses interview data collection techniques, observation, documentary studies, and questionnaires. Test data validity using source triangulation and technique. Data analysis techniques data collection, data reduction, data presentation, and conclusion. The result of the research are (1) Planning done is less, the teacher haven’t made the administration of learning such as syllabus, RPP, Prota, Promes yet. (2) Learning lesson is still less, in main activity, the teacher have not done learning apperception, when reflection and taking (3) The assessment stage is still lacking, the teacher conducts the assessment once in one semester, (4) The assessment and the lack of infrastructure, the facilities available in the field school, the ball and the racket, and even then under adverse conditions, (5) Physical fitness level of students 19 students in excellent condition, 8 students good, 2 students enough, 1 student less and 1 student in bad condition. Stage of learning in the form of planning, implementation and assessment in less category, Facilities and existing infrastructure is not sufficient for learning physical education. Physical fitness level of majority students in either category.